Association of six-minute walk distance with subsequent lower extremity events in peripheral artery disease. (August 2020) - Nayak, Pooja; Guralnik, Jack M; Polonsky, Tamar S; Kibbe, Melina R; Tian, Lu; Zhao, Lihui; Criqui, Michael H; Ferrucci, Luigi; Li, Lingyu; Zhang, Dongxue; McDermott, Mary M
The prognostic significance of the six-minute walk distance for lower extremity events in people with peripheral artery disease (PAD) is unknown. This longitudinal study assessed whether a poorer six-minute walk distance at baseline was associated with higher rates of subsequent lower extremity atherosclerotic disease events in PAD. A total of 369 patients (mean age 69.4 ± 10.0 years; mean ankle–brachial index (ABI) 0.67 ± 0.17; 31% women; 30% black individuals) from Chicago-area medical centers with PAD were enrolled. Participants underwent baseline six-minute walk testing and returned for annual study visits. Lower extremity events consisted of one or more of the following: ABI decline greater than 15% or medical record adjudicated lower extremity revascularization, critical limb ischemia, or amputation. At a mean follow-up of 33.3 months, lower extremity events occurred in 66/123 (53.7%) people in the first (worst) tertile of six-minute walk performance, 55/124 (44.4%) in the second tertile, and 56/122 (45.9%) in the third (best) tertile. After adjusting for age, sex, race, ABI, comorbidities, and other confounders, participants in the first (worst) tertile of six-minute walk distance at baseline had higher rates of lower extremity events during follow-up, compared to those in the best tertile at baseline (HR = 1.74, 95% CI 1.17–2.60, p = 0.0067). Among people with PAD, a poorer six-minute walk distance was associated with higher rates of subsequent lower extremity PAD-related events after adjusting for confounders. Further study is needed to determine whether interventions that improve six-minute walk distance can reduce lower extremity adverse events in people with PAD.